2010
DOI: 10.1074/jbc.m109.074534
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cell-derived Prostaglandin D2 Controls Hyaluronan Synthesis in Human Orbital Fibroblasts via DP1 Activation

Abstract: Thyroid eye disease (TED) is a debilitating disorder characterized by the accumulation of adipocytes and hyaluronan (HA).Production of HA by fibroblasts leads to remarkable increases in tissue volume and to the anterior displacement of the eyes. Prostaglandin D 2 (PGD 2 ), mainly produced by mast cells, promotes orbital fibroblast adipogenesis. The mechanism by which PGD 2 influences orbital fibroblasts and their synthesis of HA is poorly understood. We report here that mast cell-derived PGD 2 is a key factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 69 publications
(57 reference statements)
1
26
0
1
Order By: Relevance
“…Finally, DP 1 receptors have been implicated in the development of thyroid eye disease, which affects approximately 40% of patients with Graves hyperthyroidism. DP 1 receptors were found to be an important factor in promoting hyaluronan production, which would be a major contribution to exophthalmos (Guo et al, 2010). Thus, laropiprant would be of potential value in this debilitating ophthalmic condition.…”
Section: Distribution and Biological Functionsmentioning
confidence: 99%
“…Finally, DP 1 receptors have been implicated in the development of thyroid eye disease, which affects approximately 40% of patients with Graves hyperthyroidism. DP 1 receptors were found to be an important factor in promoting hyaluronan production, which would be a major contribution to exophthalmos (Guo et al, 2010). Thus, laropiprant would be of potential value in this debilitating ophthalmic condition.…”
Section: Distribution and Biological Functionsmentioning
confidence: 99%
“…Knockdown-We recently demonstrated that HAS2 is the dominant isoform responsible for increased HA synthesis by orbital fibroblasts in response to prostaglandin D 2 (47). To test the involvement of HAS enzymes in the TGF-␤-mediated response, siRNA was used to selectively knock down HAS1 or HAS2 mRNA levels in fibroblasts.…”
Section: Tgf-␤1-induced Adhesion Of Orbital Fibroblasts and Activatedmentioning
confidence: 99%
“…For PPAR␥ mRNA detection, 4 days after transfection, RNA was prepared as above, and PPAR␥1 and PPAR␥2 mRNA levels were analyzed using realtime PCR. HAS1 and HAS2 siRNAs (Santa Cruz Biotechnology) were also used to knock down HAS1 and HAS2 mRNA expression, respectively, as described previously (47). After 24 h of transfection, the cells were serum-starved and treated with TGF-␤1 for 24 h before further experiment.…”
Section: Mrna Knockdown Using Small Interfering Rna (Sirna)mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent report suggests that the thyrotropin receptor, the central self-antigen in Graves disease, might drive hyaluronan synthesis in orbital fibroblasts (67). Another report suggests that prostaglandin D 2 can up-regulate hyaluronan synthesis in orbital fibroblasts through the D prostanoid receptor, an induction that is attributable to HAS2 activity (68). IL-1␤ induces HAS 1, 2, and 3 mRNA levels (26) as well as UGDH expression (6) in orbital fibroblasts.…”
Section: Discussionmentioning
confidence: 99%